The Effect of Transformational Leadership and Learning Organizations through Organizational Culture as Moderation on Organizational Citizenship Behavior - Sigit Dany Setiyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The concept of Organizational Citizenship Behavior (OCB) is highly relevant to the discretion of Polri officers, especially in improving organizational performance. Three factors assumed to have a positive influence on the emergence and development of OCB in the police are namely: (1) Transformational Leadership Factor, (2) Learning Organization Factor, and (3) Organizational Culture Factor (moderating variable). Five dimensions of OCB are altruism, conscientiousness, civic virtue, sportsmanship, and courtesy. This research was conducted to examine the influence of Transformational Leadership and Learning Organizations through Organizational Culture as a moderation on OCB of POLRI officers in Resort Police environment with the predicate of Corruption-Free Region Integrity Area and/or Clean and Serving Bureaucracy Area in the East Java Regional Police Legal Area. Research respondents were 1.634 members of the National Police from seven Resort Polices in East Java Regional Police area. The sampling technique was purposive random sampling. Data processing used the Organizational Citizenship Behavior Checklist (OCB-C) instrument. The results of hypothesis testing that have been carried out using the bootstrapping method with SmartPLS 3.0 software showed that Learning Organizations and Transformational Leadership had significant positive effect on the dependent variable, namely OCB of POLRI officers, either directly or through Organizational Culture as the moderating variable.